Implementasi Pembelajaran Bahasa Arab dalam Pendidikan Islam di Indonesia - Kusaiyin Kusaiyin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2020)
Arabic learning is one of the implementations in Islamic education in Indonesia. Arabic is used as a foreign language in schools as one of the languages ​​used in Foreign Language subjects. With the existence of Islamic education in learning Arabic, it will improve Islamic writing such as Al-Qur'an, Hadith, Tafsir, Tawawuf and others. This study aims to explain the implementation of Arabic language learning in Islamic education in Indonesia while the research method used in this research is descriptive research which is able to explain the discussion to be studied. The results of this study are Arabic as one of the languages ​​that has a big role in Islamic education in Indonesia. Thus, in its implementation, Islamic education in Indonesia, especially in Arabic, is able to improve the skills and abilities of students in carrying out their activities.